Doob's ω-transform of parabolic problem for fractional Laplacian. Issue 3 (11th February 2023) - Bezzarga, Mounir; Kenzizi, Tarek; Nefzi, Chaima
Abstract : This paper studies the existence of nonnegative solutions for the following parabolic problem 1 L ω u + ∂ u ∂ t = 0, in R d × ( 0, T ), u ( x, 0 ) = u 0 ( x ), in R d, where T >0, L ω is a selfadjoint operator associated with a regular Dirichlet form Q, the initial value u 0 ∈ L 2 ( R d ), u 0 ≥ 0 is a Borel measurable function.,